2017
DOI: 10.1039/c7ra04353h
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly fabrication, microstructures and antibacterial performance of layer-structured montmorillonite nanocomposites with cationic silica nanoparticles

Abstract: Layer-structured montmorillonite nanocomposites containing cationic silica nanoparticles were fabricated for an enhancement in thermal stability and antibacterial performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…[30][31][32] SEM observation showed a three-dimensional open-porous walled structure, which was conducive to the efficient adsorption of phenol. [33][34][35] In the preparation of composite materials from dispersions, a stable and homogeneous dispersion of functional materials should be retained during the formation of polymer matrix. 24,36 In the present study, APS-derived AC was well suspended in the CA solution of a DMF/1-hexanol mixture, resulting in the good dispersion of AC on the skeleton surface of the monolith (Fig.…”
Section: Preparation and Characterization Of Ca/ac Composite Monolithmentioning
confidence: 99%
“…[30][31][32] SEM observation showed a three-dimensional open-porous walled structure, which was conducive to the efficient adsorption of phenol. [33][34][35] In the preparation of composite materials from dispersions, a stable and homogeneous dispersion of functional materials should be retained during the formation of polymer matrix. 24,36 In the present study, APS-derived AC was well suspended in the CA solution of a DMF/1-hexanol mixture, resulting in the good dispersion of AC on the skeleton surface of the monolith (Fig.…”
Section: Preparation and Characterization Of Ca/ac Composite Monolithmentioning
confidence: 99%
“…Then, polymerization occurred mostly between 450 and 650 °C. 16 In the end, the weight plots of the samples became almost flat from 650 to 800 °C because of the eventual mineralization. By comparison between the PM and PBM without chemical grafting of TPMMC, it is clear that the plasma bombardment led to a weight loss of 0.6 wt % (PM and PBM plots indicating sample weights of 90.2 and 90.8 wt %, respectively, at 650 °C), which resulted from plasma etching.…”
Section: Resultsmentioning
confidence: 97%
“…Therefore, only the two membranes demonstrated two fingerprint peaks of the C–N deformation at 1564 and 1534 cm –1 , respectively, in the inset of Figure 3 with detailed plots from 1520 to 1580 cm –1 . 1618…”
Section: Resultsmentioning
confidence: 99%
“…For instance, an interesting example on the topic is the contribution by Wang et al, who prepared hybrid composites by layer by layer assemblies of negatively charged montmorillonite and ammonium-modified silica nanoparticles. 67 As a result, their system was able to fully destroy gram-positive and gram-negative bacteria due to the quaternary ammonium-modified MSNs. In addition to the former, Michailidis et al reported a parallel strategy to coat MCM-48 MSNs with C-18 and C-14 alkyl substituted quaternary ammonium salts, although in their example a broad range biocide (Parmetol S15) was loaded into the mesopores.…”
Section: Behavior Of Polyionic Msns Against Bacteria and Biofilmsmentioning
confidence: 99%
“… Silica system modified with poly-ions. MSNs Ionic liquids Membrane lysis None None E. coli None None 66 MMT-MSN D-C18-TMSACl Membrane lysis Water-repellant None None E. coli S. aureus None None 67 MCM-48 MSN D-C18-TMSACl D-C14-TMSACl Membrane lysis Biocidal Parmetol S15 None Sea bacteria Sea cells None 110 HMSNs D-C18-TMSACl Membrane lysis Biocidal Metronidazole None S. aureus, E. coli P. gingivalis None None 68 MCM-41 MSNs ε-poly-L-lysine Membrane sensitizing HKAI pH-driven lysine detachment E. coli S. marcescens Caco-2 Zebrafish 69 MCM-41 MSNs DAMO Membrane sensitizing Levofloxacin None E. coli S. aureus None None 70 …”
Section: Behavior Of Polyionic Msns Against Bacteria and Biofilmsmentioning
confidence: 99%